2020
DOI: 10.1016/j.aninu.2020.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Over-processed meat and bone meal and phytase effects on broilers challenged with subclinical necrotic enteritis: Part 2. Inositol phosphate esters hydrolysis, intestinal permeability, hematology, jejunal gene expression and intestinal morphology

Abstract: This study investigated the hypothesis that feeding broilers over-processed meat and bone meal (MBM) would impair gut health in the absence of phytase and in turn, affect inositol phosphate (inositol x-phosphate, IPx: IP3, IP4, IP5 and IP6) ester hydrolysis, intestinal permeability, hematology, jejunal gene expression and intestinal morphology during necrotic enteritis (NE). Ross 308 male broilers ( n = 768) were assigned to one of 8 dietary treatments in a 2 × 2 × 2 factorial arrangemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 75 publications
1
8
0
Order By: Relevance
“…These findings indicated that RLS could abate intestinal permeability and lessen the degree of intestinal injury in broilers. Tight junctions, such as occludin, claudins, ZO-1, and MUC-2, are crucial components of the intestinal mucosal barrier, sustaining paracellular permeability (33). The present study found that the reduced jejunum MUC-2, clandin-1, and zonula occludens-1 mRNA expression levels were improved by RLS and antibiotics, which is in keeping with the serum DAO and D-LA concentrations of broilers.…”
Section: Discussionsupporting
confidence: 82%
“…These findings indicated that RLS could abate intestinal permeability and lessen the degree of intestinal injury in broilers. Tight junctions, such as occludin, claudins, ZO-1, and MUC-2, are crucial components of the intestinal mucosal barrier, sustaining paracellular permeability (33). The present study found that the reduced jejunum MUC-2, clandin-1, and zonula occludens-1 mRNA expression levels were improved by RLS and antibiotics, which is in keeping with the serum DAO and D-LA concentrations of broilers.…”
Section: Discussionsupporting
confidence: 82%
“…The downregulation of MUC2 in the present study because of challenge (with no antibiotic treatment) was rather unexpected as more mucin was needed to defend the mucosa. A recent study did also report the downregulation of MUC2 in the jejunum due to NE ( Zanu et al., 2020b ). It could be conjectured that as the intestine deteriorates, MUC2 expression decreases, slowing the replenishment of the mucus layer.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, in the present study, low phytase led to the upregulation of CACNA. It appears that phytase supplementation at a lower concentration upregulates the expression of calcium-related genes in broilers ( Zanu et al., 2020b ). It could be speculated that a lower phytase supplementation means lower calcium released from the diets; hence, the birds' response to increasing the expression of the related transporting genes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there was only a tendency for antibiotic addition to reduce D-LA and DAO levels, implying that dietary GP in broilers could be a good alternative to antibiotic growth promoter to protect the integrity of intestinal mucosa from LPS challenge. Tight junctions, such as occludins and claudins have been identified as crucial transmembrane proteins in intestinal mucosa, sustaining paracellular permeability [ 42 ]. MUC2 is a main part of the intestinal mucus layer and plays an important role in avoiding intestinal mucosal injury [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tight junctions, such as occludins and claudins have been identified as crucial transmembrane proteins in intestinal mucosa, sustaining paracellular permeability [ 42 ]. MUC2 is a main part of the intestinal mucus layer and plays an important role in avoiding intestinal mucosal injury [ 42 ]. We found that broilers exhibited up-regulations of jejunal MUC-2 and Claudin-1 response to LSP challenge, which was consistent with previous study [ 43 ].…”
Section: Discussionmentioning
confidence: 99%